Clinical and structural remission rates increased annually and radiographic progression was continuously inhibited during a 3-year administration of tocilizumab in patients with rheumatoid arthritis: A multi-center, prospective cohort study by the Michinoku Tocilizumab Study Group. Issue 6 (1st November 2016) - Hirabayashi, Yasuhiko; Munakata, Yasuhiko; Miyata, Masayuki; Urata, Yukitomo; Saito, Koichi; Okuno, Hiroshi; Yoshida, Masaaki; Kodera, Takao; Watanabe, Ryu; Miyamoto, Seiya; Ishii, Tomonori; Nakazawa, Shigeshi; et al.
Abstract: Objective : To evaluate the clinical and structural efficacy of tocilizumab (TCZ) during its long-term administration in patients with rheumatoid arthritis (RA). Methods : In total, 693 patients with RA who started TCZ therapy were followed for 3 years. Clinical efficacy was evaluated by DAS28-ESR and Boolean remission rates in 544 patients. Joint damage was assessed by calculating the modified total Sharp score (mTSS) in 50 patients. Results : When the reason for discontinuation was limited to inadequate response or adverse events, the 1-, 2-, and 3-year continuation rates were 84.0%, 76.8%, and 72.2%, respectively. The mean DAS28-ESR was initially 5.1 and decreased to 2.5 at 6 months and to 2.2 at 36 months. The Boolean remission rate was initially 0.9% and increased to 21.7% at 6 months and to 32.2% at 36 months. The structural remission rates (ΔmTSS/year ≤ 0.5) were 68.8%, 78.6%, and 88.9% within the first, second, and third years, respectively. The structural remission rate at 3 years (ΔmTSS ≤ 1.5) was 66.0%, and earlier achievement of swollen joint count (SJC) of 1 or less resulted in better outcomes. Conclusions : TCZ was highly efficacious, and bone destruction was strongly prevented. SJC was an easy-to-use indicator of joint destruction.